ADVANCED TEACHING METHODS FOR STUDENTS’ COMPETENCIES DEVELOPMENT - Bierne, Jekaterina; Titko, Jelena; Cerkovskis, Edgars; Lasmane, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Competence-based approach to study process is frequently discussed topic among academicians, learners and government authorities due to its practical contribution to better graduates’ employment abilities. The aim of the given study is to identify teaching methods with the biggest contribution to development of students’ competencies. Bachelor level students of management-based study courses were surveyed in order to evaluate the progress in acquiring certain management competencies. Self-evaluation study was performed before and after the course. The acquired data was processed and the contribution of analysed teaching methods to competencies’ development was assessed.